EBV-positive small cell neuroendocrine carcinoma of the nasopharynx with cervical lymph node metastasis: a case report and literature review - Xue, Jincai; Ma, Wenjuan; Liu, Xudong; Wang, Yunsheng; Wang, Xingyue; Li, Zhihu; Tian, Youxin; Liu, Qinjiang; Dong, Fang (Frontiers in Oncology, 2025)
PurposeInvestigating the diagnosis and treatment of Epstein-Barr virus-positive small cell neuroendocrine carcinomas of the nasopharynx with cervical lymph node metastasis.MethodsThe clinical data of a patient with Epstein-Barr virus-positive small cell neuroendocrine carcinoma of the nasopharynx with cervical lymph node metastasis were retrospectively analyzed, and the relevant literature was reviewed.Case presentationA 65-year-old female patient was admitted with a 1-day history of an incidentally discovered right cervical mass. Thyroid color Doppler ultrasonography revealed enlarged lymph nodes in regions II and Va of the right neck with loss of hilar structure (suspicious for metastasis). Magnetic resonance imaging demonstrated marked thickening of the bilateral nasopharyngeal walls and posterior-superior walls, with multiple enlarged lymph nodes in bilateral cervical level II regions (upper jugular chain), radiologically suggestive of metastatic involvement. Following comprehensive preoperative evaluation, the patient underwent concurrent ultrasound-guided core needle biopsy of cervical lymph nodes and endoscopic nasopharyngeal mass biopsy. The patient was pathologically diagnosed with Epstein-Barr virus-positive small cell neuroendocrine carcinoma of the nasopharynx with cervical lymph node metastasis. The patient received two cycles of etoposide-cisplatin induction chemotherapy and one cycle of targeted therapy (nimotuzumab) combined with radical radiotherapy(intensity-modulated radiation therapy, IMRT) to the nasopharyngeal and cervical lymph node regions. Follow-up magnetic resonance imaging demonstrated significant reduction in both the size of the nasopharyngeal tumor and the initially enlarged lymph nodes compared to previous scans. The patient remains on active anti-tumor therapy with ongoing clinical surveillance pending further longitudinal follow-up assessments.ConclusionEpstein-Barr virus-positive nasopharyngeal small cell neuroendocrine carcinoma is an extremely rare head and neck malignancy. Identification of this rare tumor is crucial for disease management and patient prognosis.